2016
DOI: 10.1002/jrs.4949
|View full text |Cite
|
Sign up to set email alerts
|

Portable and Raman imaging usefulness to detect decaying on mortars from Punta Begoña Galleries (Getxo, North of Spain)

Abstract: Punta Begoña Galleries were built in 1918 in Getxo (Basque Country, North of Spain) but were abandoned in 1960. Nowadays, their conservation state is very poor. In this work, portable Raman spectroscopy was applied to evaluate the original composition and possible deterioration products of the mortars used in the inner walls and those covering the concrete of the ceilings allowing us to select the most appropriate sampling points. In the laboratory, Raman microscopy and Raman imaging, assisted with scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 17 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…The sensitivity of Raman spectroscopy for low crystallized phases and the microscopic resolution fulfils the requirements for protective ability index's calculations for complex and heterogeneous corroded layers. Madariaga's group demonstrated at the laboratory and with appropriate software that the portable spectrometer is very useful to select the most representative spots for sampling and comprehensive study …”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of Raman spectroscopy for low crystallized phases and the microscopic resolution fulfils the requirements for protective ability index's calculations for complex and heterogeneous corroded layers. Madariaga's group demonstrated at the laboratory and with appropriate software that the portable spectrometer is very useful to select the most representative spots for sampling and comprehensive study …”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
“…Madariaga's group demonstrated at the laboratory and with appropriate software [114] that the portable spectrometer is very useful to select the most representative spots for sampling and comprehensive study. [114][115][116][117][118][119][120][121][122] Stone and plaster corrosion are also important questions where Raman studies can help understand mechanisms and solve problems. Using measurements being made at the laboratory on sampled fragments, Morillas et al [120][121][122] showed that a combination of X-ray fluorescence and Raman on site measurements is sufficient to draw conclusions.…”
Section: Corrosion Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia‐Florentino et al investigated the usefulness of portable and Raman imaging to detect decay on mortars from Punta Begon–a Galleries (Getxo, North of Spain). As a result of Raman, ED‐XRF and SEM‐EDS imaging, it was possible to map the distribution of the main components through the three mortar layers and also to identify the presence of dolomite {[CaMg(CO 3 ) 2 ]}, which was not possible to detect following single‐point micro‐Raman analyses . Hernanz and co‐workers described the Raman microscopy of prehistoric paintings in French megalithic monuments.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…As a result of Raman, ED-XRF and SEM-EDS imaging, it was possible to map the distribution of the main components through the three mortar layers and also to identify the presence of dolomite {[CaMg(CO 3 ) 2 ]}, which was not possible to detect following single-point micro-Raman analyses. [121] Hernanz and co-workers described the Raman microscopy of prehistoric paintings in French megalithic monuments. They conclude that the presence of pigments as decorative elements in megalithic monuments of Western France, and its possible relation with those of the Iberian Peninsula, create interesting expectations for the knowledge of the European megalithic culture.…”
Section: Glasses Ivory Resins Porcelain Pottery Bronzes Panesmentioning
confidence: 99%